IMAN AS THE FOUNDATION OF AKHLAQ IN THE PHENOMENON OF MODERN LIFE: Analysis of Said Nursi's Thought on Akhlaq (TAJDID: Jurnal Ilmu Ushuluddin, 2023)
This paper attempts to explain the role of faith as a moral principle or foundation in this modern era, according to Badi'uzzaman Said Nursi. Modern human thought and lifestyle problems occur because of the rise of secular views, which reject all metaphysical things, including values and moral studies. The purpose of this study is to analyze the elements of the relationship between Iman and morality in facing the crisis of civilization in modernity. This study is the library and qualitative research. The data collected by the researchers is in the form of a narrative and qualitative. The researchers used descriptive and content analysis methods to explain the relationship between Said Nursi's view of morality and modern human life. The approach utilized by the researcher is a Sufi philosophical approach to suit the approach used by Nursi. This paper explains that Nursi's akhlaq principles which focus on tauhid or aqidah is the basis for forming al-akhlaq al-karimah. Al-akhlaq al-karimah is one solution for the life of modern society, which is far from metaphysical values. The researchers found that iman is the basis for manifesting akhlaq to humans and nature. Researchers suggest that this research be developed and continued in more detail and detail, especially in the study of Iman and Akhlaq.Tulisan ini mencoba menjelaskan peran akidah sebagai asas atau landasan moral di era modern ini, menurut Badi'uzzaman Said Nursi. Masalah pemikiran dan gaya hidup manusia modern terjadi karena munculnya pandangan-pandangan sekular yang menolak segala hal yang bersifat metafisik, termasuk kajian nilai dan moral. Tujuan dari penelitian ini ingin menganalisa unsur-unsur keterkaitan antara iman dan akhlak dalam menghadapi krisis peradaban dalam modernitas. Penelitian ini merupakan penelitian kepustakaan dan kualitatif. Data yang dikumpulkan oleh peneliti berbentuk naratif dan kualitatif. Peneliti menggunakan metode deskriptif dan analisis isi untuk menjelaskan hubungan antara pandangan Said Nursi tentang moralitas dengan kehidupan manusia modern. Pendekatan yang digunakan peneliti adalah pendekatan filsafat-sufi yang disesuaikan dengan pendekatan yang digunakan oleh Nursi. Tulisan ini menjelaskan bahwa prinsip akhlak Nursi yang menitikberatkan pada tauhid atau akidah menjadi dasar pembentukan al-akhlaq al-karimah. Al-akhlaq al-karimah merupakan salah satu solusi bagi kehidupan masyarakat modern yang jauh dari nilai-nilai metafisik. Peneliti menemukan bahwa iman merupakan dasar untuk mewujudkan akhlak kepada manusia dan alam. Peneliti menyarankan agar penelitian ini dikembangkan dan dilanjutkan lebih detai dan terperinci, khususnya dalam kajian iman dan akhlak.